Identifikasi Struktur Modal Melalui Profitabilitas, Pertumbuhan Penjualan dan Ukuran Perusahaan - Chandrarin, Grahita; Cahyaningsih, Diyah Sukanti (AFRE (Accounting and Financial Review), 2018)
This study aims to analyze the effect of profitability, sales growth and firm size on capital structure. The population of this research is basic industrial and chemical company which go public in Bursa Efek Indonesia. The observations are conducted in 2013-2016. The data source is taken from Indonesian Capital Directory Market (ICMD). Sampling technique used with purposive sampling. The sample size is 19 companies with 4 years observation period, so there are 76 observation data. Management in determining the source of financing will consider the cost or risk with a refund. In theory, pecking order management will expose the source of internal funding, external in the form of debt, then the issuance of shares. Profitability of the company during the year 2013-2016 shows positive. Sales increase except in 2015, where sales growth is negative. Company assets show an increase every year. Data analysis techniques use multiple linear regression. The results show that profitability and sales growth affect the capital structure. The size of the firm has no effect on the capital structure. The results support the pecking order theory.Â DOI:Â  https://doi.org/10.26905/afr.v1i1.2246